DOES COVID-19 AFFECT STOCK MARKET PRICES? (Case Study on the Impact of Designating Covid-19 as a Global Pandemic) - Amsal Irmalis; Hanafi Asnan; Damrus Damrus (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2021)
This research is a case study that aims to trace market reactions caused by an event in the form of non-economic circumstances which is Covid-19.  The data used in this study is the closing price of each sectoral index from the Indonesia Stock Exchange. The data are taken cover the period of 5 days before and after the determination of covid-19 as a global pandemic. In this study hypothesis testing using paired sample t-test. , there is a significant difference in the stock price index on the Indonesian stock exchange before and after the determination of Covid-19 as a global pandemic.